High-performance composite polypropylene lithium battery diaphragm

By adopting composite polypropylene material and multi-layer structure design in the lithium battery separator, the problems of poor thermal stability, poor electrolyte wetting and insufficient mechanical strength of traditional separators are solved, and higher mechanical properties, thermal stability and electrochemical properties are achieved, extending the battery service life and improving safety performance.

CN119651059APending Publication Date: 2025-03-18JIANGXI SAIWEISI NEW ENERGY IND DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411717910.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional lithium battery separators have problems such as poor thermal stability, poor electrolyte wetting, and insufficient mechanical strength, which limits the further improvement of lithium battery performance.

Method used

A lithium battery separator made of composite polypropylene material is formed by setting micropores in the base layer, adding an inorganic coating film, an intermediate layer, a surface layer, a hydrophilic layer and a reinforcement layer between the base layers, and combining an adhesive to form a multi-layer structural separator.

Benefits of technology

It significantly improves the mechanical properties, thermal stability and electrochemical properties of the diaphragm, extends the battery life, and improves the charge and discharge efficiency and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119651059A_ABST
    Figure CN119651059A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance composite polypropylene lithium battery diaphragm, and relates to the technical field of lithium battery diaphragms.The high-performance composite polypropylene lithium battery diaphragm comprises base layers, micropores are formed in the base layers, and a middle layer is arranged between the two base layers. The base layer takes polypropylene as a main material to ensure excellent mechanical properties and thermal stability, the middle layer adopts an inorganic coating film to enhance the barrier property and thermal stability of the diaphragm, and the surface layer adopts a polytetrafluoroethylene film to improve the corrosion resistance and wettability of the diaphragm; according to the high-performance composite polypropylene lithium battery diaphragm, in order to further improve the wettability of the diaphragm to electrolyte and the ion conduction performance, the hydrophilic layer adopts polyoxyethylene, the reinforcing layer adopts a hard framework, and polyvinylidene fluoride is used as a binder, so that the structural stability and the mechanical property of the diaphragm are remarkably enhanced; the mechanical property, the thermal stability and the electrochemical performance of the battery are comprehensively improved, the service life is prolonged, and the charge-discharge efficiency and the safety performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery separators, in particular to a high-performance composite polypropylene lithium battery separator. Background Art

[0002] In the structure of lithium batteries, the diaphragm is one of the key inner components. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle and safety performance. A diaphragm with excellent performance plays an important role in improving the comprehensive performance of the battery. The main function of the diaphragm is to separate the positive and negative poles of the battery to prevent the two poles from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. The diaphragm material is non-conductive, and its physical and chemical properties have a great influence on the performance of the battery. Different types of batteries use different diaphragms.

[0003] With the rapid development of new energy vehicles, portable electronic devices and other markets, the performance requirements for lithium batteries are increasing. As one of the key components of the battery, the performance of lithium battery separators directly affects the safety, energy density and cycle life of the battery. Traditional lithium battery separators have problems such as poor thermal stability, poor electrolyte wettability, and insufficient mechanical strength, which limit the further improvement of lithium battery performance. Summary of the invention

[0004] The object of the present invention is to provide a high-performance composite polypropylene lithium battery separator to solve the technical problems raised in the above background technology.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a high-performance composite polypropylene lithium battery separator, comprising a base layer, wherein the base layer is provided with micropores inside, an intermediate layer is provided between two layers of the base layer, a surface layer is provided on the side of the base layer away from the intermediate layer, a hydrophilic layer is provided on the side of the surface layer away from the intermediate layer, and a reinforcing layer is provided on the side of the surface layer close to the hydrophilic layer through an adhesive.

[0006] Preferably, the base layer uses polypropylene as the main base material and is prepared by a solvent casting method.

[0007] Preferably, the intermediate layer is an inorganic coating film, such as ZrO 2 Or any one of aluminum oxide.

[0008] Preferably, the intermediate layer is evenly placed between the two layers of the base layer by a coating process.

[0009] Preferably, the surface layer is made of polytetrafluoroethylene film, and is coated on the upper and lower surfaces of the two layers of the base layer.

[0010] Preferably, the hydrophilic layer is made of any one of polyoxyethylene, polyethylene glycol, sodium carboxymethyl cellulose or carbomer, and is covered on the outer surface of the surface layer by a coating process.

[0011] Preferably, the reinforcement layer adopts a hard skeleton, and the reinforcement layer is evenly distributed on the surface layer.

[0012] Preferably, the binder is any one of polyvinylidene fluoride, sodium alginate, polymethyl methacrylate or styrene-butadiene rubber.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] The present invention is provided with a base layer, an intermediate layer, a surface layer, a hydrophilic layer, a binder and a reinforcing layer. The base layer is made of polypropylene as the main material and is made by a solvent casting method to ensure excellent mechanical properties and thermal stability. The intermediate layer is made of an inorganic coating film, such as ZrO 2 , and is evenly placed between the two base layers through a coating process to enhance the barrier properties and thermal stability of the diaphragm. The surface layer is made of polytetrafluoroethylene film, which is covered on the upper and lower surfaces of the polypropylene diaphragm through a coating process to improve the corrosion resistance and wettability of the diaphragm. In order to further improve the wettability of the diaphragm to the electrolyte and the ion conductivity, the hydrophilic layer is made of polyethylene oxide and covered on the outer surface of the surface layer through a coating process. The reinforcement layer adopts a hard skeleton and uses polyvinylidene fluoride as a binder to firmly and evenly bond it to the surface layer, thereby significantly enhancing the structural stability and mechanical properties of the diaphragm. This high-performance composite polypropylene lithium battery diaphragm comprehensively improves the mechanical properties, thermal stability, and electrochemical properties of the battery, extends its service life, and improves the charging and discharging efficiency and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic diagram of the three-dimensional decomposition structure of the present invention;

[0016] Figure 2 It is a schematic diagram of the three-dimensional structure of the present invention;

[0017] Figure 3 It is a schematic diagram of the three-dimensional cutaway structure of the present invention;

[0018] Figure 4 It is a top view after the present invention is split;

[0019] Figure 5 A top view of the present invention;

[0020] Figure 6 It is a top view cutaway view of the present invention.

[0021] In the figure: 1, base layer; 2, middle layer; 3, surface layer; 4, hydrophilic layer; 5, adhesive; 6, reinforcement layer; 7, micropores. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] See also Figure 1-Figure 6 The present invention provides a technical solution: a high-performance composite polypropylene lithium battery separator, comprising a base layer 1, wherein the base layer 1 is provided with micropores 7, wherein the base layer 1 uses polypropylene as the main base material and is prepared by a solvent casting method to ensure excellent mechanical properties and thermal stability;

[0024] The operating steps of the solvent casting method are as follows: select appropriate polymer materials, such as polypropylene, and necessary additives, and dissolve the polymer materials and additives in an appropriate solvent to form a uniform solution. Then, by casting, the solution is evenly spread on the mold to form a thin film. Thereafter, the solvent is gradually evaporated, and the thin film is solidified to form a preliminary diaphragm. Stretching, heat treatment and other steps are performed as needed to optimize the mechanical properties and pore structure of the diaphragm. Finally, porogens or other methods are used to form uniformly distributed micropores in the diaphragm to meet the needs of ion conduction. Through this step, a diaphragm with excellent mechanical properties and porous microstructure can be prepared so that it is suitable for electrochemical devices such as lithium batteries.

[0025] See also Figure 1-Figure 6 It can be seen that an intermediate layer 2 is provided between the two layers of the base layer 1, and the intermediate layer 2 is made of an inorganic coating film, such as ZrO 2 Or any one of aluminum oxide, the intermediate layer 2 is evenly placed between the two layers of the base layer 1 by a coating process, so as to significantly improve the thermal dimensional stability and thermal melting temperature of the diaphragm, and at the same time improve the wettability of the diaphragm to the electrolyte, improve the liquid retention capacity, thereby enhancing the puncture resistance of the diaphragm, and in addition, the comprehensive performance of the lithium battery diaphragm can be improved to meet the requirements of lithium batteries for high safety, stability and charge and discharge performance, and the coating method can be spraying, scraping, dipping;

[0026] See also Figure 1-Figure 6 It can be seen that in actual operation, the surfaces of the two layers of base 1 are ensured to be clean, flat, free of impurities and oil, and the inorganic coating material ZrO 2Evenly coat between the base layers 1 to ensure that the coating layer is uniform, free of bubbles and cracks. Repeat coating multiple times as needed to achieve the required thickness and performance. According to the requirements of the coating material, perform necessary post-processing steps such as drying and curing to ensure the stability and performance of the coating.

[0027] See also Figure 1-Figure 6 It can be seen that a reinforcing layer 6 is provided on one side of the surface layer 3 close to the hydrophilic layer 4 through a binder 5, the reinforcing layer 6 adopts a hard skeleton, and the reinforcing layer 6 is evenly distributed on the surface layer 3, and the binder 5 adopts any one of polyvinylidene fluoride, sodium alginate, polymethyl methacrylate or styrene-butadiene rubber;

[0028] See also Figure 1-Figure 6 It can be seen that adding a hard skeleton to the polytetrafluoroethylene layer and using polyvinylidene fluoride as a binder 5 is achieved through mixing, coating, drying and other processes, thereby significantly enhancing the structural stability and mechanical properties of the diaphragm;

[0029] See also Figure 1-Figure 6 It can be seen that in actual operation, polyvinylidene fluoride and hard skeleton materials are mixed, and each component is ensured to be evenly distributed, laying the foundation for subsequent processes, and the mixed material is evenly coated on the polytetrafluoroethylene layer through a coating device to form a polytetrafluoroethylene layer containing a hard skeleton and a binder, ensuring that the coating thickness is uniform to ensure the consistency of the diaphragm, and the coated diaphragm is placed in a drying device for heating and drying to fully solidify the polyvinylidene fluoride and firmly bond the hard skeleton to the polytetrafluoroethylene layer. The drying temperature and time need to be adjusted according to the specific material and process requirements to ensure the best effect. This operation process significantly enhances the structural stability and mechanical properties of the diaphragm by adding a hard skeleton and using polyvinylidene fluoride as a binder 5;

[0030] See also Figure 1-Figure 6 It can be seen that during the coating process, through a specific preparation process, the binder 5, cross-linked polymers and cross-linked compounds are "concentrated cross-linked" to improve the flexibility of the diaphragm, further disperse the external force, and improve the puncture resistance. Through this method, the high strength and puncture resistance of the polypropylene lithium battery diaphragm can be effectively improved, thereby improving the safety and overall performance of the battery.

[0031] See also Figure 1-Figure 6 It can be seen that a surface layer 3 is provided on the side of the base layer 1 away from the middle layer 2. The surface layer 3 is made of a polytetrafluoroethylene film and is covered on the upper and lower surfaces of the two layers of the base layer 1 by a coating process. The coating method can be spraying, scraping, or dipping, so as to improve the corrosion resistance and wettability of the diaphragm. In addition, the comprehensive performance of the lithium battery diaphragm can also be improved to meet the requirements of lithium batteries for high safety, stability, and charge and discharge performance.

[0032] See also Figure 1-Figure 6 It can be seen that a hydrophilic layer 4 is provided on the side of the surface layer 3 away from the middle layer 2. The hydrophilic layer 4 is made of any one of polyoxyethylene, polyethylene glycol, sodium carboxymethyl cellulose or carbomer, and is covered on the outer surface of the surface layer 3 by a coating process, so as to improve the hydrophilicity of the surface of the diaphragm, thereby further improving the wettability of the diaphragm to the electrolyte and the ion conductivity, and the coating method can be spraying, scraping, dipping;

[0033] See also Figure 1-Figure 6 It can be seen that in actual operation, ensure that the surface of the surface layer 3 is clean, flat, free of impurities and oil, and evenly coat the hydrophilic layer 4 on the surface of the surface layer 3 to ensure that the coating layer is uniform, free of bubbles and cracks. If needed, the coating can be repeated multiple times to achieve the required thickness and performance. According to the requirements of the coating material, necessary post-processing steps such as drying and curing are carried out to ensure the stability and performance of the coating.

[0034] In summary: the base layer 1 uses polypropylene as the main base material, and then a polymer material such as polypropylene is made into a base layer 1 with excellent mechanical properties and thermal stability by a solvent casting method. Subsequently, an inorganic coating film is uniformly coated as an intermediate layer 2 between the two layers of the base layer 1 by a coating process to enhance the barrier properties and thermal stability of the diaphragm. At the same time, a polytetrafluoroethylene film is covered on the upper and lower surfaces of the base layer 1 as a surface layer 3 to improve the corrosion resistance and wettability of the diaphragm. In order to further improve the wettability and ion conductivity of the diaphragm to the electrolyte, polyoxyethylene is coated on the outer surface of the polytetrafluoroethylene film as a hydrophilic layer 4. Finally, polyvinylidene fluoride is used as a binder 5 to firmly and evenly bond the hard skeleton to the polytetrafluoroethylene layer to form a reinforcement layer 6, thereby enhancing the structural stability and mechanical properties of the diaphragm. As a result, the high-performance composite polypropylene lithium battery diaphragm not only improves the mechanical properties, thermal stability and electrochemical properties of the battery, but also extends the battery life, while improving the battery charging and discharging efficiency and safety performance. The content not described in detail in this specification belongs to the prior art known to professional and technical personnel in this field.

[0035] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-performance composite polypropylene lithium battery separator, comprising a base layer (1), characterized in that: The base layer (1) is provided with micropores (7) inside, an intermediate layer (2) is provided between the two layers of the base layer (1), a surface layer (3) is provided on the side of the base layer (1) away from the intermediate layer (2), a hydrophilic layer (4) is provided on the side of the surface layer (3) away from the intermediate layer (2), and a reinforcing layer (6) is provided on the side of the surface layer (3) close to the hydrophilic layer (4) via an adhesive (5).

2. A high-performance composite polypropylene lithium battery separator according to claim 1, characterized in that: The base layer (1) uses polypropylene as the main base material and is prepared by a solvent casting method.

3. The high-performance composite polypropylene lithium battery separator according to claim 1, characterized in that: The intermediate layer (2) is made of an inorganic coating film, such as ZrO2 or aluminum oxide.

4. A high-performance composite polypropylene lithium battery separator according to claim 3, characterized in that: The intermediate layer (2) is evenly placed between the two layers of the base layer (1) by using a coating process.

5. The high-performance composite polypropylene lithium battery separator according to claim 1, characterized in that: The surface layer (3) is made of a polytetrafluoroethylene film and is coated on the upper and lower surfaces of the two layers of the base layer (1) using a coating process.

6. The high-performance composite polypropylene lithium battery separator according to claim 1, characterized in that: The hydrophilic layer (4) is made of any one of polyoxyethylene, polyethylene glycol, sodium carboxymethyl cellulose or carbomer, and is coated on the outer surface of the surface layer (3) by a coating process.

7. The high-performance composite polypropylene lithium battery separator according to claim 1, characterized in that: The reinforcement layer (6) adopts a hard skeleton, and the reinforcement layer (6) is evenly distributed on the surface layer (3).

8. The high-performance composite polypropylene lithium battery separator according to claim 1, characterized in that: The binder (5) is any one of polyvinylidene fluoride, sodium alginate, polymethyl methacrylate or styrene-butadiene rubber.